The Effect of the Role of Economic Literacy, Entrepreneurial Literacy on Young Entrepreneurial Behavior - Rahmatullah Rahmatullah; Inanna Inanna; Andika Isma; Muhammad Rahmattullah (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study aimed to analyze the effect of the role of economic literacy and entrepreneurial literacy on the entrepreneurial behavior of the younger generation. This research method used a quantitative approach with observational data collection techniques, questionnaires and documentation. The research location was carried out in the city of Makassar, Indonesia, especially in culinary entrepreneurs where there were 100 respondents who were sampled in this study and multiple linear regression as the choice of data analysis used. The results of tests conducted by using SPSS showed that simultaneously economic literacy and entrepreneurial literacy made a significant contribution to the behavior of young entrepreneurs. Partial testing gave an illustration that economic literacy had a positive effect but did not significantly influence the behavior of young entrepreneurs, different from the entrepreneurial literacy variable, it had a positive and significant effect on the behavior of young entrepreneurs in Makassar City.